GAMBARAN ASUPAN PROTEIN, ZAT BESI DAN KADAR HEMOGLOBIN PADA REMAJA PUTRI VEGETARIAN VEGAN DI INDONESIA VEGETARIAN SOCIETY (IVS) - Fitriani Fitriani; Yessi Marlina; Roziana Roziana; Dilla Rahmadini (JURNAL RISET GIZI, 2021)
Background: A vegan vegetarian is one of type indigenous vegetarians who only consume plant-based foods and its processed food products. Vegetarians tend to consume protein and iron less than RDA. Inadequate protein and iron consumption will lead to anemia. Women tend to have the highest risk for anemia, especially female adolescents.Subject: To describe protein and iron intake with HB levels in vegan vegetarian female adolescents of Indonesian Vegetarian Society (IVS) Pekanbaru.Methods: A descriptive study with cross-sectional design. The research was conducted from November 2018 to June 2019 at the secretariat of the Indonesian Vegetarian Society (IVS) Pekanbaru. The subjetcs were 22 female adolescents who were obtained by total sampling method. Hemoglobin levels were measured using easy touch GCU, dietary intake were obtained by food recall and calculated with the Nutrisurvey 2007.Result: The results showed the inadequate protein intake were 54.5%, inadequate iron intake were 68.2% and hemoglobin levels which classified as anemia were 63.63%.Conclusin: About 62.11% roespondents tend t have inadequate protein and iron intake and classified as anemia.